2004
DOI: 10.1007/bf02975883
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic coumarins from the root ofAngelica dahurica

Abstract: Ten coumarins were isolated from the root of Angelica dahurica by repeated silica gel column chromatography. Their chemical structures were elucidated on the basic of physicochemical and spectroscopic data. Among them, oxypeucedanin hydrate acetonide (7) was isolated for the first time from this plant. Cytotoxicity of coumarins isolated were determined in vitro against L1210, HL-60, K562, and B16F10 tumor cell lines by MTT method. Pangelin (5) and oxypeucedanin hydrate acetonide (7) showed a potent cytotoxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…Compounds 1-5 were identifi ed as scopoletin (Carpinella et al, 2005), aesculetin, fraxetin, fraxin and aesculin (Liu et al, 2005), respectively, by comparing their physicochemical and spectroscopic data with those published in the literature. Previously, the isolation and structural elucidation of 12 coumarins, 6-15 from A. dahurica (Thanh et al, 2004), 16 from E. daniellii (Yoo et al, 2002) and 17 from P. japonicum (Zheng et al, 2005) were reported. The chemical structures of these compounds (1-17) and four coumarins (18-21) obtained from Sigma Co. Ltd are presented in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Compounds 1-5 were identifi ed as scopoletin (Carpinella et al, 2005), aesculetin, fraxetin, fraxin and aesculin (Liu et al, 2005), respectively, by comparing their physicochemical and spectroscopic data with those published in the literature. Previously, the isolation and structural elucidation of 12 coumarins, 6-15 from A. dahurica (Thanh et al, 2004), 16 from E. daniellii (Yoo et al, 2002) and 17 from P. japonicum (Zheng et al, 2005) were reported. The chemical structures of these compounds (1-17) and four coumarins (18-21) obtained from Sigma Co. Ltd are presented in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The fraction F.6 was purifi ed on an LH-20 column (7.5 × 30 cm) and eluted with MeOH-H 2 O (4 : 1) to yield compounds 4 (2.5-2.8 L, 36 mg) and 5 (3.0-3.2 L, 21 mg Compounds 6-21. The isolation and structural elucidation of compounds 6-15 from the Korean medicinal plant Angelica dahurica were reported previously (Thanh et al, 2004), including isoimperatorin (6), osthol (7), imperatorin (8), psoralen (9), pangelin (10), bergapten (11), oxypeucedanin hydrate acetonide (12), oxypeucedanin (13), xanthotoxin (14), and oxypeucedanin hydrate (15). Two coumarins, isopimpinellin (16) and (+)-marmesin (17) were isolated from E. daniellii (Yoo et al, 2002) and P. japonicum (Zheng et al, 2005), respectively.…”
Section: Isolation Of Coumarins Frommentioning
confidence: 99%
“…Limited studies were performed to evaluate the effects of Angelicae dahuricae radix on the cell viability in vitro and in vivo (14,15), and Angelicae dahuricae radix extract showed cytotoxicity toward cancer cells, including mouse lymphocytic leukemia cells, human promyelocytic leukemia cells, human myelogenous leukemia cells, and mouse melanoma cells (14). Coumarins were isolated from Angelicae dahuricae radix by silica gel column chromatography, and the half maximal inhibitory concentration (IC 50 ) values varied from 8.6 to 14.6 µg/ml cells.…”
Section: Discussionmentioning
confidence: 99%
“…4). 92 Sapogenins Sapogenins, such as triterpenoid saponins (8) and diterpenes (9) exert a wide range of immunomodulatory activities. Examples are Gymnema sylvestre, Chlorophytum borivilianum, Boswellia spp.…”
Section: Coumarinsmentioning
confidence: 99%